The effect of taxes on the debt policy of spanish listed companies - José A. Clemente-Almendros; Francisco Sogorb-Mira (SERIEs - Journal of the Spanish Economic Association, 2016)
This study explores the role of taxes in explaining companies' financing decisions. We test whether the corporate tax shields explanation of capital structure is applicable to firms listed on the Spanish stock exchange over the period 2007-2013. Taxes are found to be economically and statistically significant determinants of capital structure. Our results suggest that marginal tax rates affect the debt policies of Spanish listed companies, and the existence of non-debt tax shields constitutes an alternative to the use of debt as a tax shelter. Consistent with theoretical expectations, there is a stronger relation between debt and taxation in less levered firms. Finally, we empirically estimate the impact of the new thin-capitalization rule put forth by the Spanish government in 2012 on the financing behaviour of Spanish listed companies. Our empirical evidence supports the existence of a tax reform effect, where companies affected by interest deductibility limitations reduce their leverage more than companies that are not affected.
Keywords: C33; G32; H25; 330; Capital structure; Corporate taxes; Debt; Marginal tax rate; Thin-capitalization rule